Dikyasa Unit’s Efforts to Prevent Motor Vehicle Accidents in the Karawang Police Legal Area - Juniarto, Very Rahmawan (Police Studies Review, 2024)
The advancement of transportation facilities in the form of motor vehicles has not been matched by an increase in legal awareness and traffic discipline among motor vehicle users. This has led to a rise in the number of traffic violations. In fact, every road user is obligated to participate in maintaining a conducive, orderly, safe, and smooth traffic situation. Therefore, the problem addressed in this thesis is: “What are the efforts of the Dikyasa Unit in preventing traffic accidents involving motor vehicles in the jurisdiction of Polres Karawang?” The objective of this research is to describe the traffic accidents occurring in the jurisdiction of Polres Karawang and the efforts of the Dikyasa Unit in preventing these accidents. The research literature referenced includes studies by Syafar Irfan (2016) and Fajar Syaeful (2015), from which similarities in research on traffic have been obtained. The difference in this thesis is that the author focuses on the activities of Dikmas Lantas in preventing traffic accidents in the jurisdiction of Polres Karawang. The concepts and theories that serve as the basis for this research include Management Theory from Terry, Communication Theory from Hafied Cangara, and the concept of Dikmas Lantas in the Vademikum Lantas (2009). Based on the research findings and discussion, it can be concluded that traffic accidents in Karawang Regency from 2016 to 2019 have increased. In 2016, the number of accidents reached 540 cases, while in 2019, the number rose to 816 cases. This increase is attributed to human factors, natural factors, vehicle factors, and road infrastructure factors. The Dikyasa Unit’s efforts to prevent traffic accidents include preemptive measures, conducting traffic discipline outreach; preventive measures by installing traffic discipline warning banners at several accident-prone locations, and patrolling these areas. Supporting factors for the Dikmas Lantas activities include the enthusiasm of the members and well-planned activities in accordance with applicable procedures. Meanwhile, hindering factors include budget constraints and the still low level of community awareness regarding traffic discipline. Therefore, the recommendations include the need to propose a special budget for Dikmas Lantas activities and to conduct socialization of Dikmas Lantas for the community using banners and utilizing social media.